2006
DOI: 10.1038/ng1739
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic control of Caenorhabditis elegans fat storage

Abstract: Tubby mice and individuals with Bardet-Biedl syndrome have defects in ciliated neuron function and obesity, suggesting an as-yet unknown metabolic signaling axis from ciliated neurons to fat storage tissues. Here we show coordinate regulation of Caenorhabditis elegans fat storage by orthologues of these genes acting in ciliated neurons and by a 3-ketoacyl-coA thiolase (encoded by kat-1) that acts in fat storage tissue. A genetic screen for markedly enhanced fat storage in tub-1 mutants led to the isolation onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
158
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(173 citation statements)
references
References 30 publications
14
158
0
1
Order By: Relevance
“…Animals with compromised chemosensory neuron structure and/or function are small and accumulate fat [25][26][27][28][29]. A TGF-β signaling pathway has been implicated in regulating body size [30], and the DBL-1 TGF-β ligand is neuronally expressed [31].…”
Section: The Importance Of Chemosensationmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals with compromised chemosensory neuron structure and/or function are small and accumulate fat [25][26][27][28][29]. A TGF-β signaling pathway has been implicated in regulating body size [30], and the DBL-1 TGF-β ligand is neuronally expressed [31].…”
Section: The Importance Of Chemosensationmentioning
confidence: 99%
“…However, it is not yet clear whether chemosensory inputs function via modulation of the dbl-1 TGF-β pathway or via alternate pathways to regulate body size. A neuroendocrine signal from the chemosensory neurons released in response to external or internal nutrient signals has been proposed to regulate fat storage in the intestine [27][28][29], but pathway components have not yet been defined. As the requirement of chemosensation in regulating body size and fat storage may be independent of the ability of animals to locate food sources or the rate of food consumption and storage, internal metabolic state may be altered by chemosensory perception to regulate cell size and fat metabolism [26,27].…”
Section: The Importance Of Chemosensationmentioning
confidence: 99%
“…43 Mutation of the 3-ketoacyl-coA thiolase (kat-1) gene is associated with increased fat storage in tissue owing to impairment of fat oxidation, and decreased kat-1 activity appears to be responsible for the increased fat accumulation in tub-1-mutant C. elegans. 44 Specifically, tub-1 interacts with a Rab-GTPase-activating protein (RBG-3) to regulate fat storage by controlling receptor or sensory molecule degradation in neurons, and by upregulating the activity of a small C. elegans in obesity research J Zheng and FL Greenway Rab-GTPase (RAB-7) to mediate an endocytic pathway that increases fat storage. 45 Taken together, mutations of tub-1 result in increased fat storage in C. elegans through a decrease in KAT-1 activity, which impairs fat oxidation and through an increase in fat storage by enhanced endocytosis.…”
Section: Serotoninmentioning
confidence: 99%
“…45 Taken together, mutations of tub-1 result in increased fat storage in C. elegans through a decrease in KAT-1 activity, which impairs fat oxidation and through an increase in fat storage by enhanced endocytosis. 44 The human adipose gene (Adp) dose dependently suppresses obesity. The othologs of the Adp gene are conserved in other species as well as in C. elegans (Y73E7A.9), in flies (adpr-1) and in mice (Wdtc1).…”
Section: Serotoninmentioning
confidence: 99%
“…The bbs-1 gene, which could synergisticly increase fat storage in a kat-1 mutant, has been identified by genetic screen. This gene acts in 15 ciliated neurons, and regulates fat storage in the same pathway as that of tub-1 [9] . In addition, studies have revealed that the classical neurotransmitters have dramatic effects on fat regulation in nematodes [10,11] .…”
mentioning
confidence: 99%